Tracing Digital Collusion: A Forensic Legal Framework for Asset Recovery in Indonesian E Commerce - Wahyuningsih (Summa : Journal of Accounting and Tax, 2024)
Seller collusion on e commerce platforms undermines fair competition and creates measurable risks for financial integrity and erodes consumer trust. This study investigates Indonesia’s capacity to trace and recover assets derived from such digital collusion by evaluating the legal, forensic, and institutional frameworks currently in place. Methodologically, the study combines doctrinal legal analysis with digital forensic protocols under ISO/IEC 27037. It draws from three empirical datasets: seller account metadata, financial transaction flows (VA, e wallet, bank accounts), and enforcement records (seizures, freeze orders, beneficial ownership disclosures). The analysis is further contextualized through international case studies from the United Kingdom and the United States. Results show that Indonesia's existing legal instruments such as the Anti Money Laundering Law (UU 8/2010), KUHAP Articles 39/46, and Perpres 13/2018 on Beneficial Ownership are theoretically adequate but operationally underutilized. Institutional silos, lack of real time data access, and limited forensic capabilities hamper timely asset tracing. However, evidence from forensic analytics such as synchronized pricing, mutual refund loops, and shared account linkages offers a viable pathway for detection. AI based tools and graph analytics are identified as valuable enablers. The discussion emphasizes the importance of regulatory synchronization, risk based privacy access models, and alignment with global best practices (e.g., POCA, BSA). Successful asset tracing also hinges on adherence to the Personal Data Protection Law (UU 27/2022), requiring encryption, pseudonymization, and strict access governance. The study concludes that an integrated framework combining legal reform, forensic capacity building, and ethical data governance is essential for Indonesia to enhance its digital asset recovery strategy.